General practitioners' views on retaining Singapore's primary care doctors: a cross-sectional survey and qualitative analysis - Fang, Yang (2022)
Background: To support its ageing population and the increasing need for chronic care in the community, Singapore needs to boost the number of doctors in its primary care workforce. To better understand how to improve doctor retention and build a more robust primary care system, we conducted a cross-sectional survey with doctors in general practice and family medicine to explore their career satisfaction, their career plans, factors related to their plans to leave, and their view on retaining GPs in primary care. Methods: An anonymous online survey was distributed to general practitioners working in the public and private sectors. The survey contained questions on career satisfaction, career plans in the next 5 years, and factors important for retaining doctors in primary care. In addition, there were open-ended questions for respondents to elaborate on retention initiatives and other factors that may improve engagement among primary care doctors. Quantitative data was analyzed with descriptive statistics, principal component analysis, χ2 tests, t-tests, and Pearson’s correlations; qualitative data was analyzed thematically. Results: The survey was attempted by 355 general practitioners and completed in full by 303. The respondents were most satisfied with rapport with patients and their current professional role; they were least satisfied with the amount of paperwork and the status of general practice in society. In terms of their career plans in the next 5 years, 49/341 (14.4%) of the respondents plan to leave general practice permanently, 43/341 (12.6%) plan to take a career break, and 175/341 (51.3%) plan to reduce their clinical hours. Higher remuneration, recognizing general practice and family medicine as a medical specialty, and reducing the litigious pressures on medical practice were rated as the most important factors for retaining primary care. Free-text responses also revealed a growing dissatisfaction with the Third Party Administrators that manage insurance arrangements. Conclusion: While the proportion of doctors who intend to leave is smaller than that reported in overseas studies, our findings highlight an urgent need for targeted interventions to engage and retain primary care doctors. Increasing recognition and support for general practitioners and their professional practice may contribute to strengthening community care for the ageing population.